2012
DOI: 10.1016/j.ijrobp.2011.06.1958
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Detection and Real-Time DMLC Adaptation to Target Rotation During Radiotherapy

Abstract: SummaryCurrent-day radiotherapy systems do not account for tumor rotation, and dosimetric errors may result. This study reports a system that integrates a prototype electromagnetic tracking system to detect tumor translation and rotation with a dynamic multileaf collimator system that in real-time adapts the radiation beam to the translation and rotating tumor. Results show a rotation accuracy correction error of less than 1 degree. Dosimetric studies showed a three-fold improvement in target dose accuracy com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…However, the other forms of target motion also widely exist. It has been reported that large perpendicular translational motion10 and large rotational motion11 are likely to cause very low efficiency. Therefore, it is worth studying whether the HS‐MLC is capable to compensate for other forms of target motion without loss of efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the other forms of target motion also widely exist. It has been reported that large perpendicular translational motion10 and large rotational motion11 are likely to cause very low efficiency. Therefore, it is worth studying whether the HS‐MLC is capable to compensate for other forms of target motion without loss of efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, MLC tracking is realized through dynamically adapting the aperture to the moving target, which does not rely on margin enlargement or beam hold‐offs (unless large position error occurs) in contrast to the first two. Previous studies have applied MLC tracking to dealing with different forms of target motion: one‐dimensional (1D) translation,3, 4, 5, 6 two‐dimensional (2D) translation,7, 8, 9 three‐dimensional (3D) translation,10 rotational motion11 and deformation 12…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been several studies that have utilized Calypso‐generated rotational offsets to evaluate PTV margins and dosimetric coverage for prostate radiotherapy 20, 21, 22, 23. These studies show that target rotations can cause significant target under‐dosing even when translations are corrected for, with negative effects complexly linked to a combination of the magnitude of rotation, target shape and the distance between the target and transponders’ rotational centroid (eccentricity) 20, 22.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this paucity of evidence evaluating the accuracy of transponder‐based systems like Calypso in measuring rotational offsets, the authors note that a number of recent studies have used Calypso‐generated localization data to draw conclusions on margin calculations and dosimetric coverage 20, 21, 22, 23. For example, the results of one study using this rotational offset information suggested that inter‐ and intrafraction prostatic rotations may result in target underdosing in up to 61% of patients depending on the PTV expansion used 20.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, no real-time information on target rotational motion is visible to the user in the Calypso system or the CyberKnife system during prostate treatments. However, increasing evidence suggests that intrafractional tumour motion corrections should be applied to both tumour translations and tumour rotations [16][17][18]. Off-line post-treatment calculation of tumour rotations have shown that the rotations could be significant for both prostate and lung tumours [16,19].…”
Section: Introductionmentioning
confidence: 99%